Toward Defining the Neural Substrates of ADHD: A Controlled Structural MRI Study in Medication-Naïve Adults. (November 2015) - Makris, Nikos; Liang, Lichen; Biederman, Joseph; Valera, Eve M.; Brown, Ariel B.; Petty, Carter; Spencer, Thomas J.; Faraone, Stephen V.; Seidman, Larry J.
Objective: We assessed the neural correlates of adult ADHD in treatment-naïve participants, an approach necessary for identifying neural substrates unconfounded by medication effects.Method: The sample consisted of 24 medication-naïve adults with Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV ) diagnosed ADHD and 24 healthy controls, comparable on age, sex, handedness, reading achievement, IQ, and psychiatric comorbidity. All participants were assessed with structured diagnostic interviews. Magnetic resonance imaging (MRI)-based regional voxel-based morphometry (r-VBM) was used to assess volumetric differences in a priori defined brain regions of interest.Results: VBM analysis revealed group differences in the hypothesized cortical and subcortical areas; however, only cerebellar volume reductions in ADHD retained significance ( p < .05) after corrections for multiple comparisons.Conclusion: These results support the notion that medication-naïve ADHD as expressed in adulthood, manifests subtle brain volume reductions from normal in the cerebellum, and possibly in other syndrome-congruent gray-matter structures. Larger samples are required to confirm these findings.